Lower versus standard sucrose dose for treating hypoglycemia in patients with type 1 diabetes mellitus in therapy with predictive low glucose suspend (PLGS) augmented insulin pumps: A randomized crossover trial in Santiago, Chile. Issue 3 (May 2021) - Grassi, Bruno; Onetto, María Teresa; Zapata, Yazmín; Jofré, Paulina; Echeverría, Guadalupe
Abstract: Background and aims: Recommended hypoglycemia treatment in adults with T1D consists of 15 g of rapid absorption carbohydrates. We aimed to evaluate the response to fewer carbohydrates for treating hypoglycemia in patients with T1D on insulin pumps with predictive suspension technology (PLGS). Methods: T1D patients on insulin pumps with PLGS were randomized to receive 10 or 15 g of sucrose per hypoglycemia for two weeks (S10 and S15 groups, respectively) when capillary blood glucose (BG) was <70 mg/dL, with crossover after two weeks. Evolution of capillary BG, active insulin, and suspension time were assessed. Results: 59 hypoglycemic episodes were analyzed, 33 in S10 and 26 in S15. Baseline BG in S10 was 54.3 ± 7.7 mg/dL versus 56.9 ± 8.8 in S15 (p = 0, 239). Active insulin, present in 85% of the episodes, and PLGS suspension time were similar between groups. BG at 15 min was 77 mg/dL in S10 and 95 mg/dL in S15 (p = 0.0007). In S10, 21% of the episodes required to repeat the treatment after 15 min compared with none on S15, with a RR of 0, 79 (95% CI 0.66, 0.940, p = 0, 014) for successfully treating the episode. Sensor glucose was significantly different from BG at the moment of the hypoglycemia and control 15 min after treatment. No severe hypoglycemia and no rebound hyperglycemia occurred in neither group. Conclusions: A hypoglycemia treatment protocol with a lower dose of sucrose might be insufficient despite PLGS technology. Our data suggest that standard doses of sucrose should still be recommended. Highlights: Despite insulin suspension technology, reducing the sucrose dose used for a hypoglycemia might result in treatment failure. Adult patients with T1D should use standard doses of sugar to treat hypoglycemia, even when PLGS technology is available. Sensor glucose values should not be used for diagnosing and/or deciding to treat hypoglycemia.